2012
DOI: 10.3126/ijosh.v2i2.6596
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Prevalence of Musculoskeletal Disorders among the Coalminers of Eastern Coalfields of India

Abstract: Background: Mining is an ancient occupation, long recognized as being arduous and liable to injury and disease. The lifecycle of mining consists of exploration, mine development, mine operation, decommissioning and land rehabilitation. Objective: To explore the prevalence characteristics and influence factors related to the development of work related musculoskeletal disorders of underground coalminers in Eastern Coalfield mines. Methods: In a cross-sectional study of 55 coalminers from Saatgram Project, Ranig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A high prevalence of musculoskeletal disorders (MSDs) has been reported amongst miners in several countries (Bandyopadhyay, Dev & Gangopadhyay 2012 ; Widanarko et al 2015b ; Xu et al 2012a ). Low back pain reported amongst miners in various countries has ranged from 23% in Indonesian miners to 78% in Turkish miners (Bandyopadhyay et al 2012 ; Bio et al 2007 ; Sarikaya et al 2007 ; Widanarko et al 2013 ; Xu et al 2012a ). Pain in other anatomical sites such as the neck, shoulder, wrist and leg has also been reported amongst Indian coal miners (Bandyopadhyay et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of musculoskeletal disorders (MSDs) has been reported amongst miners in several countries (Bandyopadhyay, Dev & Gangopadhyay 2012 ; Widanarko et al 2015b ; Xu et al 2012a ). Low back pain reported amongst miners in various countries has ranged from 23% in Indonesian miners to 78% in Turkish miners (Bandyopadhyay et al 2012 ; Bio et al 2007 ; Sarikaya et al 2007 ; Widanarko et al 2013 ; Xu et al 2012a ). Pain in other anatomical sites such as the neck, shoulder, wrist and leg has also been reported amongst Indian coal miners (Bandyopadhyay et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain reported amongst miners in various countries has ranged from 23% in Indonesian miners to 78% in Turkish miners (Bandyopadhyay et al 2012 ; Bio et al 2007 ; Sarikaya et al 2007 ; Widanarko et al 2013 ; Xu et al 2012a ). Pain in other anatomical sites such as the neck, shoulder, wrist and leg has also been reported amongst Indian coal miners (Bandyopadhyay et al 2012 ). The nature of underground mining activities presents several physical and psychosocial risks for workers, which have been associated with work-related MSDs (Widanarko et al 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…2% of the participants belonged to 45-50 years of age and the mean age of the study population was 45.6±7.56 years 3. Mean age of the study participants was 26.25±8.49 years, 43.83±9.33 years and 31±6.38 years in studies by Adsul et al, Bandyopadhyay et al and Gosh et al respectively [17][18][19]. Education About, 46.8% had studied upto middle school, 29.2% had studied upto primary school and 9.1% were illiterates in our study.…”
mentioning
confidence: 99%
“…Such risk factors in this occupational group have led to many problems for them. For example, studies have shown that the mining industry had the second highest incidence ratio for low back disorders (1.5 claims/100 workers), trailing only to the construction industry (1.6 claims/100 workers) (14). Therefore, evaluating these jobs with the purpose of design and implementation of appropriate ergonomic interventions for improving their working conditions seems to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Mining jobs are such that workers are exposed to numerous ergonomic risk factors such as poor postures, use of improper tools, and excessive force in different parts of the body (14,15). Such risk factors in this occupational group have led to many problems for them.…”
Section: Introductionmentioning
confidence: 99%